Development and characterization of a novel injectable thyroid extracellular matrix hydrogel for enhanced thyroid tissue engineering applications - Zhang, Liang; Long, Houlong; Zhang, Peng; Liu, Bin; Li, Shuheng; Sun, Rong; Diao, Tongmei; Li, Feng (Frontiers in Bioengineering and Biotechnology, 2024)
Hypothyroidism, a condition characterized by decreased synthesis and secretion of thyroid hormones, significantly impacts intellectual development and physical growth. Current treatments, including hormone replacement therapy and thyroid transplantation, have limitations due to issues like hormone dosage control and immune rejection. Tissue engineering presents a potential solution by combining cells and biomaterials to construct engineered thyroid tissue. This study focuses on the development and characterization of a novel 3D injectable hydrogel derived from thyroid extracellular matrix (TEM) for thyroid tissue engineering. TEM hydrogels were prepared through decellularization of rat thyroid tissue, followed by extensive physicochemical and mechanical property evaluations. The TEM hydrogels exhibited properties similar to natural thyroid tissue, including high biocompatibility and a complex 3D ultrastructure. Thyroid hormone-secreting cells cultured in TEM hydrogels demonstrated superior viability, hormone secretion, and thyroid-related gene expression compared to those in traditional type I collagen hydrogels. The study also confirmed the significant retention of key growth factors and ECM proteins within the TEM hydrogels. The results indicate that TEM hydrogels can provide a biomimetic microenvironment, promoting the long-term survival and function of thyroid cells, thus holding great promise for the treatment of hypothyroidism. This research contributes a potential new avenue for thyroid tissue engineering, offering a promising alternative for hypothyroidism treatment.